Development of a LINE Chatbot (CAREBOTX) for Providing Information on Specialized Medications - Fhakfaipouk, Boonsita; Tangjitwattanakorn, Watcharapong; Baiklai, Sakolwan; Phetmanee, Surasak; Phetmanee, Thidarat (Interprofessional Journal of Health Sciences, 2025)
This descriptive study aimed to develop a LINE chatbot to provide information on the use of specialized medications and to assess user opinions and satisfaction at Rangsit University. The researcher developed the chatbot using Google Sheets as a medication database and integrated Google Apps Script with the Messaging API and Webhook to enable user interactions. The chatbot was designed to retrieve information on specialized medications on the basis of trade names or categories, including details on dosage forms, usage instructions, and demonstration videos. Data on user opinions and satisfaction were collected from 221 volunteers aged 18 and older, excluding healthcare personnel and health sciences students. Among the 300 recruited participants, 221 met the inclusion criteria and completed an online questionnaire via Jotform. The results indicated that users highly rated the chatbot in terms of content, application, efficiency, and system accessibility. Overall satisfaction with the LINE chatbot was also rated very positively. In conclusion, this study demonstrated that CAREBOTX is an accurate, user-friendly tool for providing information on specialized medication use, making it highly suitable for individuals requiring specialized medications.